Rate of improvement of CF life expectancy exceeds that of general population: observational death registration study - Hurley, Matthew; McKeeve, Tricia M.; Prayle, Andrew P.; Smyth, Alan R.; Fogarty, Andrew W. (Elsevier, 2014)
Background: It is unclear why cystic fibrosis (CF) survival has improved. We wished to quantify increases in CF median age of death in the context of general population survival improvement. Method: Death registration data analysis (US, England & Wales (E&W)—1972–2009). Results: CF median age of death is higher in US than E&W and greater for males, opposite to that of death from all causes. CF median age of death has increased by 0.543 life years per year (E&W, US combined (95% confidence interval 0.506, 0.582)). The difference in median age at death between those dying from all causes and CF decreased in both territories. CF median age of death for males is greater than for females in both territories. This gap has not narrowed. Conclusion: The median age of death of people with CF is improving more rapidly than that of the general population in US and E&W.